2021
DOI: 10.3389/fimmu.2021.748019
|View full text |Cite
|
Sign up to set email alerts
|

Acute Graft-Versus-Host Disease, Infections, Vascular Events and Drug Toxicities Affecting the Central Nervous System

Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) is a curative therapy for patients with hematological malignancies. Acute Graft versus host diseases (GVHD) is a major immune mediated side effect of allo-HCT that can affect the central nervous system (CNS) in addition to post-allo-HCT vascular events, drug toxicity or infections. Here we summarize and discuss recent preclinical data on the CNS as a target of acute GVHD and the known mechanisms contributing to neurotoxicity with a focus on microglia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 91 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Clinical manifestations of CNS-GVHD include seizures, vision loss, aphasia, and cognitive impairment. The symptoms are similar to multiple sclerosis or Guillain-Barre syndrome (6,8). Transplantation-associated thrombotic microangiopathy (TA-TMA) has been shown to be another rare potential neurological complication of allogeneic stem cell transplantation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations of CNS-GVHD include seizures, vision loss, aphasia, and cognitive impairment. The symptoms are similar to multiple sclerosis or Guillain-Barre syndrome (6,8). Transplantation-associated thrombotic microangiopathy (TA-TMA) has been shown to be another rare potential neurological complication of allogeneic stem cell transplantation (9).…”
Section: Discussionmentioning
confidence: 99%
“…10 T-cell infiltration through blood-brain barrier leads to IL-6 and indoleamine 2,3 deoxygenase production. 11 This likely has central role in CNS GvHD due to its action on host microglial cells. Hence, therapies that suppress T-cell infiltration and block IL-6 could reverse neuroinflammation.…”
Section: Extensive Evaluation Included An Electroencephalogram (Eeg)mentioning
confidence: 99%
“…While typical manifestations of acute GVHD and other NRM are thought to involve the skin, gastrointestinal tract, and liver, more recent reports have suggested that symptoms arising from central nervous system derangements may be a significant complication of immune therapies such as HSCT. Of these, a recent case report identified autoimmune limbic encephalitis (LE) as a complication of allogeneic HSCT [ 6 ]. LE is an inflammatory disease of the medial temporal lobes mediated by autoantibodies such as antibodies to N-methyl-D-aspartate (NMDA)-type glutamate receptor (GluR) or human herpesvirus 6 (HHV-6) and has often been reported as a paraneoplastic syndrome [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%